2002
DOI: 10.1021/es0157907
|View full text |Cite
|
Sign up to set email alerts
|

Occurrence and Destruction of PAHs, PCBs, ClPhs, ClBzs, and PCDD/Fs in Ash from Gasification of Straw

Abstract: Two experiments were performed with an atmospheric circulating fluidized bed gasifier (ACFBG), the first with pelletized straw and the second with loose straw, to investigate the occurrence of polycyclic aromatic hydrocarbons (PAHs), chlorophenols (CIPhs), polychlorinated biphenyls (PCBs), polychlorinated benzenes (ClBzs), polychlorinated dibenzo-p-dioxins (PCDDs), and polychlorinated dibenzofurans (PCDFs) in the bottom ash and fly ash formed during gasification. Only PAHs were present in large amounts, and on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(4 citation statements)
references
References 18 publications
1
3
0
Order By: Relevance
“…The dioxin concentration of the product gas was 0.5 ng TEQ/Nm 3 where no OLGA was applied, while it was a factor 10 lower when the gas was purified using the OLGA scrubber. Other measurements presented in the plot are within the acceptable limit, thanks to rapid gas cooling [67].…”
Section: Overview Of Experimental Measurements Of Dioxin Formation Le...supporting
confidence: 60%
“…The dioxin concentration of the product gas was 0.5 ng TEQ/Nm 3 where no OLGA was applied, while it was a factor 10 lower when the gas was purified using the OLGA scrubber. Other measurements presented in the plot are within the acceptable limit, thanks to rapid gas cooling [67].…”
Section: Overview Of Experimental Measurements Of Dioxin Formation Le...supporting
confidence: 60%
“…PAHs released into the environment are due to natural processes and anthropogenic sources such as waste incineration, coal gasification and accidental oil spills (Asikainen et al, 2002;Law et al, 2002;Koh et al, 2004). Different authors have reported the presence of PAHs in waters, marine organisms and sediments (Senthil Kumar et al, 2008;Massara Paletto et al, 2008;Francioni et al, 2007;Boscolo et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…The test demonstrated that small quantities of pollutants, and particularly air toxics, are present in the syngas. Polyaromatic hydrocarbon formation, which could be of concern in the ash as demonstrated in the gasification of other types of waste, 37 was not addressed. During the tests conducted, the oil feed rate increased from 56.9 to 60.6 kg/hr, which, in turn, represented a decrease in the heating value and an increase in the chlorine of the feed mixture, with a corresponding decrease in the relative amounts of carbon and hydrogen present in the oil.…”
Section: Discussionmentioning
confidence: 99%